Positive possibilities of rethinking (urban) mathematics education within a postmodern frame - Walshaw M (Georgia State University, 2011)
Postmodernism and mathematics education are both crucial components of contemporary society, yet they have rarely addressed each other. Coupling mathematics education with postmodernism allows us to explore what positive possibilities might ensue for the discipline in general and for urban schools in particular beyond the traditional contours of mathematics education. In discussing the postmodern potential, we first need to be clear about modernist thinking. That discussion takes us back to Decarte’s search for certainty, order, and clarity – a search that was integral to the formulation of a modernist framework in the 17th century. For that time until recently, most Western thinkers understood reality as characterised by an objective structure, accessed through reason by an autonomous subject. These characteristically modernist beliefs have tended to shape thinking about knowledge, representation, and subjectivity within the Western intellectual tradition of which mathematics education is a part. During the 1960s a number of literacy critics began writing about the limitations of modernist thinking. Postmodern sensibilities then emerged and entered the full range of human sciences. This emergence was most keenly expressed through the publication of Jean-Francois Lyotard’s (1984) The Postmodern Condition: A Report on Knowledge. In this work, Lyotard argued that the ‘grant narratives’ of Western history and, a particular, enlightened modernity, had broken down. Multiple factors have brought about postmodernism. They include political and social crises of legitimation, and the resulting changing nature of economies and social structures in Western societies. These changes place complex and sometimes conflicting demands on people in ways that they are barely able to understand or predict. For example, increasingly, within mathematics education, we are becoming aware of the complex construction of our work emerging from, among other things, new forms of inclusive political tendencies, changing vocational needs, and advances in informatics and communication systems. The effects of these processes for mathematics education are unsettling. Conceptual tools and frameworks from postmodern thinking help us to develop an understanding of those effects. They help us to understand ideas that are central to mathematics education from beyond the standard categories of thought. In particular, they help us to understand cognition and subjectivity.